Action of Small Entrepreneurs to Deal with the Risk of Pandemic Covid-19 - Nurul Hidayah Harahap; Pristiyono Pristiyono; Mulya Rafika; Fauziah Hanum Rambe (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Covid-19 phenomenon in Indonesia has had a very big effect, especially on small traders in Labuhanbatu Regency, the main reason for this study to measure the extent to which possible aspects affect the welfare of small traders in the Glugur Rantauprapat Market amidst the Covid-19 storm. This research was conducted in Glugur Market, Rantauprapat City, Labuhanbatu Regency, a sample of 130 traders using purposive sampling technique with survey data collection techniques both from primary data and secondary data. The primary data source uses an instrument in the form of a questionnaire containing statement indicators that are distributed to respondents who are determined based on criteria. Meanwhile, data analysis used IBM SPSS & AMOS path analysis. Based on the coefficient value of the trading hours variable path to the income variable is --0.724 with a p-value (0,469) > 0.05, which means it is not significant. Based on the path coefficient value of the capital variable on the income variable, it is 0.701 with a p-value (0,001) < 0.05, which means it is significant. Based on the path coefficient value of the trading experience variable on the income variable, it is 0.281 with a p-value (0,033) < 0.05, which means it is significant. Based on the path coefficient value of the income variable to the welfare variable, it is 0.388 with a p-value (0,000) < 0.05, which means it is significant.